Evaluation Of BPJS Patient Satisfaction Level With Pharmaceutical Services At Grandmed Lubuk Pakam Hospital - Irmayani .; Nurjannah Syafitri (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Quality health care is the most important thing in the healthcare industry. Quality health services are characterized by a sense of satisfaction felt by patients through health care in accordance with standards and codes of ethics. There are 5 indicators used to measure patient satisfaction including reliability, responsiveness, empathy, confidence and direct evidence. This study aims to evaluate the level of satisfaction of BPJS patients with pharmaceutical services at Grandmed Lubuk Pakam Hospital. The research used quantitative research with a descriptive approach that aims to evaluate BPJS patient satisfaction in pharmaceutical services at Grandmed Lubuk Pakam Hospital. The research was conducted at Garndmed Lubuk Pakam Hospital. The population in this study were all outpatient BPJS patients who received pharmaceutical services at Grandmed Lubuk Pakam Hospital, totaling 122 people with a sample of 34 people who were taken using accidental sampling technique. Data collection uses primary and secondary data. Primary data was obtained through direct interviews with BPJS patients using a formatted questionnaire, while secondary data was obtained from the patient's medical records, then the data were analyzed descriptively and presented in the frequency distribution table. The results showed that on average (73.5%) outpatient BPJS patients were satisfied with pharmaceutical services at Grandmed Lubuk Pakam Hospital in terms of reliability, responsiveness, trust, empathy, and physical evidence. Pharmacists are expected to continue to provide the best service to patients.